2018
DOI: 10.1016/j.tibs.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Greasing the Wheels of Lipid Biology with Chemical Tools

Abstract: Biological lipids are a structurally diverse and historically vexing group of hydrophobic metabolites. Here, we review recent advances in chemical imaging techniques that reveal changes in lipid biosynthesis, metabolism, dynamics, and interactions. We highlight tools for tagging many lipid classes via metabolic incorporation of bioorthogonally functionalized precursors, detectable via click chemistry, and photocaged, photoswitchable, and photocrosslinkable variants of different lipids. Certain lipid probes can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 82 publications
0
64
0
1
Order By: Relevance
“…Another factor key to the development of optoPLD was IMPACT, a chemical biology tool that we had originally designed to study the activity and localization of endogenous mammalian PLDs ( Bumpus and Baskin, 2016 , 2017 , 2018 ). Here, we confirmed that IMPACT could be applied to quantify the activity of an exogenous, bacterial PLD within mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor key to the development of optoPLD was IMPACT, a chemical biology tool that we had originally designed to study the activity and localization of endogenous mammalian PLDs ( Bumpus and Baskin, 2016 , 2017 , 2018 ). Here, we confirmed that IMPACT could be applied to quantify the activity of an exogenous, bacterial PLD within mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, optoPLD is a tool for precise, spatiotemporally controlled production of local pools of PA on individual organelle membranes that should complement existing toolsets for modulating PA using inhibition or knockout/knockdown of biosynthetic enzymes. OptoPLD interfaces with a variety of imaging-based tools for monitoring the dynamics of PA metabolism, including genetically encoded biosensors, FRET-based imaging of PLD–substrate binding events, and our recently developed chemoenzymatic method, IMPACT ( Zhang et al, 2014 ; Kassas et al, 2012 , 2017 ; Bumpus and Baskin, 2018 ; Kim et al, 2015 ; Lu et al, 2016 ; Hughes et al, 2002 ). We validated the physiological relevance of optoPLD-derived PA pools to confirm and elucidate differential roles of PA signaling in the modulation of Hippo signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Localized production or accumulation of intracellular signaling agents is a key feature of signal transduction pathways. Chemical imaging tools have helped pave the way to understand biological signaling pathways dependent on second messengers (2)(3)(4)66). We initiated this study with the goal of establishing an activity-based imaging tool to enable precise monitoring of the production of the lipid second messenger PA by PLD enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids are hydrophobic biomolecules that can be broadly divided by their chemical composition into three main categories: simple lipids (eg, triglycerides, TGs), compound lipids (eg, sphingolipids) and derived lipids (eg, cholesterol). 18 However, most lipids are stored in adipose tissue in the form of the simple lipid TG. There are two main sources of lipids in the body: dietary intake and in vivo synthesis.…”
Section: Mechanisms By Which Pcbs Affect Hepatic Lipid Accumulationmentioning
confidence: 99%